Ambient Air Levels and Trends of Polychlorinated Biphenyls at Four Different Sites - Cindoruk, S. Siddik; Tasdemir, Yucel (SPRINGER, 2010)
In this study, samples were collected in order to determine atmospheric levels of polychlorinated biphenyls (PCBs) in four different sites by using a high-volume air sampler (HVAS). Eighty-three congeners of gas and particle- phase PCBs were investigated in air samples. The total (gas + particle) concentrations for Mudanya (coastal), Butal (traffic/urban), the Uludag University Campus (semirural), and Yavuz Selim (residential) were determined as 570, 394, 412, and 316 pg/m(3), respectively. These levels coincide with the values reported for the sites having similar characteristics. In terms of homolog groups, 3-chlorinated biphenyls (3-CBs) and 4-CBs constituted at least 47% of the total PCB concentration. PCBs in all sites were determined mostly in the gas phase, with a percentage from 85 to 95%. Obtained atmospheric PCB data were correlated with meteorological parameters and a significant relationship was obtained between coastal and semirural sites (p < 0.05). With the movements of air transportation and wind rose possible data sources of PCBs were enlightened. Partitioning of gas/particle was examined with available models; significant relationships were determined for coastal and semirural sites especially.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; POLYBROMINATED DIPHENYL ETHERS; WATER-SURFACE SAMPLER; PHASE PCB CONCENTRATIONS; ORGANOCHLORINE PESTICIDES; PARTITION-COEFFICIENT; ATMOSPHERIC PCBS; LAKE-MICHIGAN; BALTIC SEA; GAS/PARTICLE CONCENTRATIONS; Environmental Sciences & Ecology; Toxicology